PERANCANGAN, PELATIHAN, DAN PENDAMPINGAN MANAJEMEN JURNAL BERBASIS OPEN JOURNAL SYSTEM PADA PENGELOLA JURNAL RENAI : LEMBAGA PERCIK SALATIGA - Barkhowa, Mokhammad Khukaim; Isitiani, Ambar; Prastiyo, Angga; Indriastuti, Adelia (Fokus ABDIMAS, 2025)
This community service activity is partnered with Persemaian Cinta Kemanusiaan (Percik) Salatiga. The purpose of this community service activity is to provide an understanding to the Manager of the Renai Persemaian Cinta Kemanusiaan (Percik) Journal regarding the features and design of the Open Journal System. Provide an understanding to the Manager of the Renai Persemaian Cinta Kemanusiaan (Percik) Journal regarding the requirements for managing the Open Journal System. Provide an understanding to the Manager of the Renai Persemaian Cinta Kemanusiaan (Percik) Journal regarding national and international accreditation standards and to be able to independently publish the Renai journal. The results of this community service activity have several things achieved. The design was successfully carried out through an open journal system but experienced obstacles regarding hosting and e-ISSN registration. The training went smoothly, participants were open-minded about the importance of switching to electronic journals, but there were still obstacles so that this renai journal could accommodate non-academic writers. Mentoring went smoothly, journal managers understood the procedures for submission, editing, journal settings, categories, websites, workflows and users & roles.Keywords: Open Journal System, Design, Training and Mentoring